Hypertonia, Microcephaly And Hyperkalaemia In A Neonate: Coexistence Of Neurodevelopmental Disorder And Adrenal Insufficiency - R, Usha Devi; Nirmalan Dhakshanamoorthy; Prakash Amboiram; Umamaheswari Balakrishnan (Iranian Journal of Child Neurology, 2022)
In neonates with more than one clinical abnormality, we always look for a unifying diagnosis that explains the entire clinical presentation. In rare instances, two conditions can co-exist. Here we report a neonate born out of consanguineousmarriage presenting at 48 hours of life with microcephaly, encephalopathy, hypertonia. He had excessive weight loss,persistent hyperkalaemia, shock and 17- hydroxyprogesterone was elevated. Steroids were started for adrenal insufficiency. Magnetic resonance imaging (MRI) of the brain revealed T2 hyperintensity of cerebral white matter and cerebral atrophy. Clinical exome sequencing (CES) revealed a pathogenic homozygous missense variation of CYP21A2 gene responsible for congenital adrenal hyperplasia and also a homozygous missense variant of unknown significance (VUS) of VARS gene implicated in Neurodevelopmental disorder with microcephaly, seizures, and cortical atrophy (NDMSCA). Baby was neurologically abnormal at discharge. In the setting of consanguinity, there is a possibility of two genetic conditions. Clinical exome sequencing is useful in demystifying the diagnosis in complex clinical presentation.